STRATEGI KOMUNIKASI PEMASARAN PERSONAL SELLING PADA PKT-KEBUN RAYA BOGOR - Detya Wiryany (ArtComm, 2018)
Bogor Botanical Garden (BBG) is the center of the plants conservation that is under the auspices of scientific institution Indonesia LIPI. In improving service quality to the society BBG, was creating a sub section that oversees the information and services by a personal selling. To optimized personal selling activities, can't be separated from the role of personal selling division. Their roles are to present the personal selling and to promote products to prospective society. Personal selling activities as a direct interaction with the potential customers ere making presentations, promoting and takeing orders. Personal selling have barriers that non technical and technical barriers. A succesful buisness has always been marked by high sales. Marketing is the only reason why business can generate very high sale while competitor lower. Only by recognizing the core of marketiing activities we can get the optimal sales for our business. Persuasive communication is, communication that aims to alter or affect the beliefs, attitudes and behaviour of a person acting in accordance with what is expection by communicator. In presenting information, messages or information to customers which required a personal selling in influencing coustomers servic user. They are traying to made the consumen give a positive responses to personal selling. Therefore communication for information is must do by comunicatif so it can be understood by the consumen. Keywords: bogor botanical garden, persuasive communication, marketing, personal selling